FAKTOR PREDIKSI HASIL UJI TUBERKULIN POSITIF ANAK SD DI KABUPATEN CILACAP TAHUN 2008 - Sri Nurlaela; Dyah Umiyarni Purnamasari; Erna Kusumawati; Dwi Sarwani Sri Rejeki; Setiyowati Rahardjo (Kesmas Indonesia, 2010)
TB of children in community show of TB case's proportion which will occur in the future.Besides, TB of children 's distribution could be the indicator of the ongoing transmission of TB in the community. This study conducted to explore the prediction factor of positive tuberculin tedt which were children's characteristic (age, gender), parent's characteristic (parent's education ,parent's occupation) and household size. A case control study held in primary school children attending class I-IV (8-13 years age) in Kabupaten Cilacap from September - Desember 2008. Sample divided in two group, there are 109 case 109 control. School children two had result of tuberculin test ≥ 10 mm, respectively, were considered as a case. Control were school children who have result of tuberculin test 0-9 mm, selected by proportional random sampling. Informations about children's results of tuberculin test were obtained from secondary data of tuberculin data survey which held on center Java. Primary data obtained by interviewing of school children. Logistic regression demonsrtated prediction factors of positive tuberculin test were BCG scar (p value = 0,049, OR= 0,432, 95% CI = 0,250-0,753) and age (p value= 0,003, OR= 0,434, 95% CI= 0,187 - 0,996).